2020
DOI: 10.1080/14786419.2020.1723087
|View full text |Cite
|
Sign up to set email alerts
|

Hexane fraction from Brazilian Morus nigra leaves improved oral carbohydrate tolerance and inhibits α-amylase and α-glucosidase activities in diabetic mice

Abstract: Morus nigra, popularly known as mulberry, has been traditionally used as anti-diabetic herbal medication. This study focused on hexane fraction from Brazilian M. nigra leaves (Hex-Mn) effects on digestion and absorption of carbohydrate in diabetic mice.The high-performance liquid chromatography (HPLC) analysis was performed, and showed the presence of flavonoids isoquercetin and kaempferol-3-O-rhamnoside. Hex-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The n-hexane component of Morus alba has also been demonstrated to lower blood glucose in mice. In a diabetic mouse model, the n-hexane extract of Morus alba was administered and found to delay the digestion and absorption of carbohydrates, reduce postprandial blood glucose values and inhibit the activity of α-glucosidase ( Silva et al, 2021a ). The extract was obtained by extracting mulberry leaves with ethanol and 48 rats were grouped and treated by gavage for 11 weeks, after which the islet β-cell function, insulin resistance index, fasting blood glucose, plasma insulin levels and the histomorphology of islets were measured.…”
Section: In Vitro and In Vivo Evaluation ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The n-hexane component of Morus alba has also been demonstrated to lower blood glucose in mice. In a diabetic mouse model, the n-hexane extract of Morus alba was administered and found to delay the digestion and absorption of carbohydrates, reduce postprandial blood glucose values and inhibit the activity of α-glucosidase ( Silva et al, 2021a ). The extract was obtained by extracting mulberry leaves with ethanol and 48 rats were grouped and treated by gavage for 11 weeks, after which the islet β-cell function, insulin resistance index, fasting blood glucose, plasma insulin levels and the histomorphology of islets were measured.…”
Section: In Vitro and In Vivo Evaluation ...mentioning
confidence: 99%
“…Researchers used column chromatography to elute and separate the aqueous extract of mulberry leaves to obtain flavonoids including rutin, isoquercitrin, kaempferol-3-0-rutinoside and astragaloside, and used these compounds to conduct in vitro α-glucosidase inhibition experiments using microplate method, and found that these compounds The inhibition rates of these compounds were found to be dose-dependent for α-glucosidase,Their IC 50 values were 13.19 ± 1.10, 116.7 ± 1.17, 365.4 ± 1.05 and 15.82 ± 1.11 μM respectively ( Hong et al, 2013 ). In addition to the inhibition of α-glucosidase by extraction of the aqueous fraction, the flavonoids obtained from the extracted fraction of mulberry leaves with non-polar components were administered to diabetic mice, and after a period of treatment, the oral carbohydrate tolerance and blood glucose values of the diabetic mice were improved, and the activities of α-amylase and α-glucosidase were inhibited ( Silva et al, 2021a ). It has also been shown that the addition of flavonoid components (5,6,7-trihydroxyflavone sapogenins) to 1-DNJ-containing diets can have a synergistic effect by increasing the inhibition of α-glucosidase by 1-DNJ, probably due to the fact that flavonoid sapogenins can act as an inhibitor that can bind to the non-competitive position of maltosidase-glucoamylase, allowing 1-DNJ to interact with α-glucoamylase.…”
Section: Molecular Mechanism Of Hypoglycemia In Mulberry Leavesmentioning
confidence: 99%
“…In this context, in Brazil, there are several medicinal plants that are used as herbal medicines by the rural and urban populations (Dutra et al, 2016;Pio et al, 2019). A single species can produce numerous chemical compounds with diverse pharmacological activities (Mendonça et al, 2019), including antibacterial (Pandini et al, 2018;Emre et al, 2020;Pacheco et al, 2020), anti-inflammatory (Ribeiro et al, 2018;Almohawes and Alruhaimi, 2020), antioxidant (Barth et al, 2018;Pontes et al, 2019;Vale et al, 2019), wound-healing properties (Ribeiro Neto et al, 2020), antihyperglycemic effect (Silva et al, 2020), and cardiovascular activity (Moreira et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The plant leaves constitute quercetin and chlorogenic acid (Zeni et al, 2017), and the fruit has keracyanin, kuromanin, cyanidin, cyanidin‐3‐glucoside (C3G), cyanidin‐3‐xyloside, and cyanidin‐3‐rutinoside (Suttisansanee et al, 2020; Yazdankhah et al, 2019). Other constituents are isoquercitrin, kaempferol‐3‐ O ‐rhamnoside (Silva et al, 2020), gallic acid, catechin, and rutin (Diab et al, 2020). Moreover, M. nigra fruit is a potential source of anthocyanins (Aybastier, 2021).…”
Section: Introductionmentioning
confidence: 99%